The Effect of Promotion, Consumer Engagement, and Social Networking Content on Brand Loyalty with Brand Trust as an Intervening Variable (Circles Bakery Case Study) - Dhega, Cornelia Ical; Ningrum, Nonik Kusuma; Maharani, Bernadetta Diansepti (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to determine (1) whether Promotion has a positive and significant effect on brand loyalty with brand trust as an intervening variable, (2) whether consumer engagement has a positive and significant effect on brand loyalty with brand trust as an intervening variable, (3) whether SNS Content has a positive and significant effect on brand loyalty with brand trust as an intervening variable, (4) whether brand trust has a positive and significant effect on brand loyalty. The sample in this study was 112 Circles Bakery customers. The data collection method used a questionnaire distributed using Google Forms. The research method used was a purposive sampling technique. The data obtained from the questionnaire were then processed and analyzed by Multiple Linear Regression with model accuracy (classical assumption test), hypothesis testing using a partial test (t) and a determination test (R2) using the SPSS 30 program. The results of this study indicate that the promotion variable has a positive and significant effect on brand trust, the consumer engagement variable has a positive and significant effect on brand trust, SNS content does not have a positive and significant effect on brand trust, the brand trust variable has a positive and significant effect on brand loyalty, and the promotion variable has a positive and significant effect on brand loyalty through brand trust as an intervening variable. Consumer engagement has a positive and significant effect on brand loyalty through brand trust as an intervening variable, and SNS content has a positive and significant effect on brand loyalty through brand trust as an intervening variable.